500 likes | 1.01k Views
Quadratic Equation– Session 3. Session Objective. 1. Condition for common root. 2. Set of solution of quadratic inequation. 3. Cubic equation. Condition for Common Root. _H007. The equations ax 2 + bx + c = 0 & a’x 2 + b’x + c’ = 0 has a common root(CR) .
E N D
Session Objective 1. Condition for common root 2. Set of solution of quadratic inequation 3. Cubic equation
Condition for Common Root _H007 The equations ax2 + bx + c = 0 & a’x2 + b’x + c’ = 0 has a common root(CR) a 2 + b + c = 0 a’ 2 + b’ + c’ = 0 Treating 2 and as two different variable By rule of cross-multiplication ab’–ba’ bc’–cb’ ca’–ac’
Condition for Common Root _H007 Condition for common root ofax2 + bx + c = 0 & a’x2 + b’x + c’ = 0 is (ca’-ac’)2=(bc’-cb’)(ab’-ba’)
Illustrative Problem _H007 If x2-ax-21=0 and x2-3ax+35=0 (a>0)has a common root then value of a is (a)3 (b) 4 (c )2 (d) 4
Illustrative Problem If x2-ax-21=0 and x2-3ax+35=0 (a>0)has a common root then value of a is (a)3 (b)4 (c )2 (d)4 _H007 Solution: Method 1 Let be the common root 2-a -21=0 2-3a+35=0 By Cross- Multiplication
Illustrative Problem _H007 If x2-ax-21=0 and x2-3ax+35=0 (a>0)has a common root then value of a is (a)3 (b) 4 (c )2 (d) 4 a2=16 a = 4 As a>0 a=4
Illustrative Problem _H007 If x2-ax-21=0 and x2-3ax+35=0 (a>0)has a common root then value of a is (a)3 (b) 4 (c )2 (d) 4 Solution: Method 2 2- a - 21 = 0 ….(A) 2-3a+35 = 0 …..(B) (A) – (B) 2a = 56 Substituting ‘’ in (A) a = 4 As a>0 a=4
Illustrative Problem _H007 If equation x2-ax+b=0 and x2+bx-a=0 has only one common root then prove that a-b=1 Solution: By observation at x=1 both the equation gives same value. x2- ax + b=0 …(A) L.H.S. = a-b-1 for x=1 x2 + bx - a=0 …(B) This means x=1 is the common root a – b – 1= 0 a–b=1 Why? for x=1 both the equations give this
Illustrative Problem _H007 If equation x2-ax+b=0 and x2+bx-a=0 has only one common root then prove that a-b=1 Solution: Method 2 • Let be the common root then • 2 -a + b = 0 & • 2 + b - a = 0 subtracting one • from the other we get • (b + a) - (b + a) = 0 • = 1 provided b + a 0 Hence x = 1 is the common root 1 – a + b = 0 or a – b = 1 Why??
Condition for Two Common Roots _H007 The equations ax2+bx+c=0 and a’x2+b’x+c’ = 0 have both roots common ax2 + bx + c K(a’x2 + b’x + c’) why? when both the roots are common ,two equations will be same . But not necessarily identical. As x2–3x+2=0 and 2x2–6x+4=0 Same equation. Both have roots 1,2 But not identical For two roots to be common
Illustrative Problem _H007 • If x2+ax+(a-2) = 0 and bx2+2x+ 6 = 0 have both roots common then a : b is • (a) 2 (b)1/2 (c) 4 (d)1/4 Solution: As both roots are common a=-1
ax2+bx+c > 0 ax2+bx+c 0 Quadratic Inequation _H009 A statement of inequality exist between L.H.S and R.H.S Quadratic Inequation If ax2+bx+c =0 has roots ,; let < ax2+bx+c = a(x- )(x- ) When ax2+bx+c >0 Let a>0 (x- )(x- )>0
- Number line Quadratic Inequation _H009 (x- )(x- )>0 Either (x- )>0; (x- )>0 Or (x- )<0; (x- )<0 x > and x> x<< x < and x< x>> x< x> • and are not included in set of solutions for a(x- )(x- )>0 ; (a>0) x lies outside ,
- 1/3 1/2 Illustrative Problem _H009 Find x for which 6x2-5x+1>0 holds true Solution: for 6 (x-1/3) (x-1/2)>0 Either x>1/2 or x<1/3
- Quadratic Inequation _H009 ax2+bx+c = a(x- )(x- ) and a>0 where < When ax2+bx+c < 0 (x- )(x- ) < 0 Either (x- )<0; (x- )>0 Or (x- )>0; (x- )<0 x > and x< x < and x> <x< No solution • and are not included in set of solutions <x< for a(x- )(x- ) <0 ; (a>0) x lies within ,
x 1/3 1/2 Illustrative Problem _H009 Find x for which 6x2-5x+1<0 holds true Solution: for 6 (x-1/3) (x-1/2)<0 1/3 <x< 1/2
- -2 3 Illustrative Problem _H009 Solve for x : x2 - x – 6 > 0 Solution: Step1:factorize into linear terms (x-3) (x+2) >0 Step2 :Plot x for which x2-x–6=0 on number line x2-x–6 >0 for either x<-2 or x>3 As sign of a >0
x x Quadratic Inequation _H009 For a(x- )(x- ) 0 x x Here set of solution contains , and all values outside , For a(x- )(x- ) 0 x x lies within , and also includes , in solution set
Illustrative Problem _H009 Solution : x2 – 8x + 10 0 step1: Find the roots of the corresponding equation Roots of x2 – 8x + 10 = 0 are
- 4-6 4+6 Illustrative Problem _H009 x2 – 8x + 10 0 Step2: Plot on number-line 4-6 and 4+6 are included in the solution set
- 7 8 Illustrative Problem _H009 Solve for x : - x2 +15 x – 6 > 0 Solution: Here a=-1 Step1: Multiply the inequation with (-1)to make ‘a’ positive. Note- Corresponding sign of inequality will also change x2 –15 x + 6 < 0 (x-7)(x-8) <0 step2: Plot on Number line 7 <x<8
Cubic Equation _H015 P(x)=ax3+bx2+cx+d A polynomial of degree 3 P(x)=0 ax3+bx2+cx+d=0 is a cubic equation when a 0 Number of roots of a cubic equation?
Cubic Equation _H015 Let the roots of ax3+bx2+cx+d =0 be ,, ax3+bx2+cx+d a(x- ) (x- ) (x- ) As ax2+bx+c has roots , can be written as ax2+bx+c a(x- ) (x- ) a[x3-(++)x2+(++)x-()]
Cubic Equation _H015 ax3+bx2+cx+d a[x3-(++)x2+ (++)x-()] Comparing co-efficient
Cubic Equation _H015 ax3+bx2+cx+d=0 a,b,c,dR 3 Maximum real root = ? As degree of equation is 3 Minimum real root? 0? Complex root occur in conjugate pair when co-efficient are real Maximum no of complex roots=2 Minimum no. of real root is 1
Illustrative Problem _H015 If the roots of the equation x3-2x+4=0 are ,, then the value of (1+ ) (1+ ) (1+ ) is • 5 (b) –5 • (c )4 (d) None of these
Illustrative Problem _H015 If the roots of the equation x3-2x+4=0 are ,, then the value of (1+ ) (1+ ) (1+ ) is (a)5 (b)–5 (c )4 (d) None of these Solution Method 1: x3-2x+4=0 has roots ,, a=1, b=0, c=-2, d=4 (1+ ) (1+ ) (1+ )= 1+ + + =1-0-2-4 = -5
Illustrative Problem _H015 If the roots of the equation x3-2x+4=0 are ,, then the value of (1+ ) (1+ ) (1+ ) is • 5 (b) –5 (c )4 (d) None of these Method 2 Let f(x)= x3-2x+4 = (x- ) (x- )(x- ) for x=-1 f(-1)= 5 = (-1- ) (-1- )(-1- ) (-1)3(1+ ) (1+ )(1+ ) = 5 (1+ ) (1+ )(1+ ) = -5
Class Exercise1 • If the equations ax2 + bx + c = 0 and cx2 + bx + a = 0 have one root common then • a + b + c = 0 • a + b – c = 0 • a – b + c = 0 • both (a) or (c) Solution: • By observation roots of one equation is • reciprocal to other. So both equation will have common root if it becomes 1 or –1
Class Exercise1 • If the equations ax2 + bx + c = 0 and cx2 + bx + a = 0 have one root common then • a + b + c = 0 • a + b – c = 0 • a – b + c = 0 • both (a) and (c) When 1 is common root ,a + b + c = 0. when –1 is common root, a – b + c = 0
Class Exercise2 • If x2 + ax + 3 = 0 and bx2 + 2x + 6 = 0 have both roots common then a : b is • (a) 2 (b)1/2 (c) 4 (d)1/4 Solution: As both roots are common
Class Exercise3 Solution : x2 – 10x + 22 0 Factorize into linear terms by using perfect square method
x 5-3 5+3 Class Exercise3 Plot on number-line 5-3 and 5-3 are included in the solution set
Class Exercise4 • The number of integral values of x for which (x – 6) (x + 1) < 2 (x – 9) holds true are • (a) Two (b)Three (c) One (d) Zero Solution: (x – 6) (x + 1) < 2 (x – 9) x2 – 7x + 12 < 0 or, x2 – 5x – 6 < 2x – 18 or, (x – 3) (x – 4) < 0 3 < x < 4 • So no integral values of x satisfies it.
If , , are the roots of 2x3 + 3x2 – 2x + 1 = 0. Then the value of is • 17/4 (b) 41/4 • (c )9/4 (d) None of these Class Exercise5 2x3 + 3x2 – 2x + 1 = 0 Solution:
Class Exercise5 If , , are the roots of 2x3 + 3x2 – 2x + 1 = 0. Then the value of is • 17/4 (b) 41/4 • (c )9/4 (d) None of these
Class Exercise6 If ax2 + bx + c = 0 & bx2 + c x + a = 0 has a common root and a ‡ 0 then prove that a3+b3+c3=3abc Solution: (bc – a2)2 = (ab – c2) (ac – b2)
Class Exercise6 If ax2 + bx + c = 0 & bx2 + c x + a = 0 has a common root and a ‡ 0 then prove that a3+b3+c3=3abc (bc – a2)2 = (ab – c2) (ac – b2) By expansion: b2c2 + a4 – 2a2bc = a2bc – ab3 – ac3 + b2c2 a(a3 + b3 + c3) = 3a2bc a(a3 + b3 + c3 – 3abc) = 0 either a = 0 or a3 + b3 + c3 = 3abc As a 0 a3 + b3 + c3 = 3abc
Class Exercise7 Find the cubic equation with real co-efficient whose two roots are given as 1 and (1 + i) Solution: • Imaginary roots occur in conjugate pair; when co-efficients are real Roots are 1, (1 – i) (1 + i) • Equation is or, (x – 1) (x2 – 2x + 2) = 0 x3 – 3x2 + 4x – 2 = 0
Class Exercise8 If ax3 + bx2 + cx + d = 0 has roots , and and , then find the equation whose roots are Solution: As roots are incremented by 2. • So desired equation can be found replacing x by (x– 2) • a(x – 2)3 + b(x – 2)2 + c(x – 2) + d = 0
Class Exercise9 Find values of x for which the inequation (2x – 1) (x – 2) > (x – 3) (x – 4) holds true Solution: (2x – 1) (x – 2) >(x – 3) (x – 4) 2x2 – 5x + 2 > x2 – 7x + 12 x2 + 2x – 10 > 0
Class Exercise9 Find values of x for which the inequation (2x – 1) (x – 2) > (x – 3) (x – 4) holds true
Class Exercise10 • For what values of ‘a’ , • a(x-1)(x-2)>0 when 1 < x < 2 • (a) a > 0 (b) a < 0 (c) a = 0 (d) a = 1 Solution: When 1 < x < 2 (x – 1) > 0, (x – 2) < 0 As a (x – 1) (x – 2) > 0 a < 0